2016
DOI: 10.1007/s11102-016-0777-3
|View full text |Cite
|
Sign up to set email alerts
|

Benzene and 2-ethyl-phthalate induce proliferation in normal rat pituitary cells

Abstract: PurposeEndocrine disruptors are known to modulate a variety of endocrine functions and increase the risk for neoplasia. Epidemiological data reported increased prevalence of pituitary tumors in high industrial areas while genotyping studies showed that mutations in the aryl hydrocarbon receptor (AhR) interacting protein (AIP)—chaperone to the dioxin ligand AhR—gene are linked to predisposition to pituitary tumor development. Aim of the present study was to establish whether endocrine pollutants can induce cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Finally, none of the tested pollutants affected cell growth or viability. Recently, Tapella et al (2016) reported that 96 hour in vitro treatment with either BZ (250 pM-1.25 nM) or DEHP (250 pM -1.25nM) was able to increase cell viability and proliferation of primary cultures obtained from normal rat pituitary tissue. This different behavior may be explained by different exposure times or the different models used; pollutants could interfere with the growth of normal cells; whereas, the absence of effects on cancerous cells, may be due to an already dysregulated cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, none of the tested pollutants affected cell growth or viability. Recently, Tapella et al (2016) reported that 96 hour in vitro treatment with either BZ (250 pM-1.25 nM) or DEHP (250 pM -1.25nM) was able to increase cell viability and proliferation of primary cultures obtained from normal rat pituitary tissue. This different behavior may be explained by different exposure times or the different models used; pollutants could interfere with the growth of normal cells; whereas, the absence of effects on cancerous cells, may be due to an already dysregulated cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The authors therefore hypothesized the involvement of environmental pollutants in the pathogenesis of somatotropinomas. Recently, Tapella et al (2016) demonstrated in vitro that the pollutants BZ and DEHP are able to interfere with normal rat pituitary cell proliferation and to promote gene expression changes at AIP and AHR levels, providing a link between epidemiological and genomic findings in pituitary tumors. However, to date, there are no other studies about the influence of these environmental chemical pollutants on the behavior of pituitary tumors in terms of aggressiveness and potentially drug therapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The first recognized partner of AIP is the nuclear receptor AhR, known to bind environmental toxins. The role of the AhR-AIP pathway has been studied in pituitary cells and patients with acromegaly ( 42 , 43 , 44 , 45 , 46 , 47 , 48 ). Several in vitro studies have related exposure to AhR-mediated toxins in GH3 cells to an increase in either proliferation ( 47 ) or GH secretion ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the AhR-AIP pathway has been studied in pituitary cells and patients with acromegaly ( 42 , 43 , 44 , 45 , 46 , 47 , 48 ). Several in vitro studies have related exposure to AhR-mediated toxins in GH3 cells to an increase in either proliferation ( 47 ) or GH secretion ( 48 ). An epidemiological association was proposed between exposition to environmental pollution and somatotropinoma incidence ( 43 ), although no direct link was found in the area with an inductrial accident involving dioxin ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the challenge of creating a structured database on solvents from thousands of journal articles, predicting their endocrine disrupting (ED) nature is equally a tough ask. Although the examination of their ED nature is found in some studies [54,55,56,57,58,59,60]…”
Section: Nlp Language Modelsmentioning
confidence: 99%